Immunoassay of serum conjugates of cholic acid in cystic fibrosis. Issue 4 (April 1980) - Davidson, G P; Corey, M; Morad-Hassel, F; Sondheimer, J M; Crozier, D; Forstner, G G
Abstract : Pre- and post-prandial serum conjugates of cholic acid (SCCA) were measured by radioimmunoassay (RIA) in 83 patients with cystic fibrosis (CF), 14 of whom did not have steatorrhoea, and in 25 controls. Of the CF patients with steatorrhoea, 38% had fasting SCCA levels greater than 3 standard deviations above mean fasting control values, whereas no CF patient without steatorrhoea had elevated fasting SCCA levels. Steatorrhoeic patients with palpable livers had higher pre- and post-prandial SCCA levels. Post-prandial SCCA levels failed to discriminate between control and CF groups however. Other serum tests of liver function, including the aspartate amino transferase, alkaline phosphatase, albumin, gamma globulin, and albumin : globulin ratio, failed to correlate with the SCCA. Changes in serum protein constituents correlated strongly with pulmonary dysfunction. The results suggest that elevation of fasting SCCA levels in CF patients is a more sensitive indicator of liver dysfunction than other tests and is a better discriminator than post-prandial SCCA levels between normal and abnormal liver function. The test is recommended for early detection of liver dysfunction in CF patients.